2012
DOI: 10.1002/ptr.4651
|View full text |Cite
|
Sign up to set email alerts
|

Screening Indian Plant Species for Antiplasmodial Properties – Ethnopharmacological Compared with Random Selection

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…In this study, the good level of antiplasmodial activity showed by the MeOH extract of E. scaber leaf (EC 50 = 0.27 μg/ml) was contradictory to the study reported by Kantamreddi and Wright [ 46 ]. According to Kantamreddi and Wright [ 46 ], the MeOH extract of the leaves of this plant was considered inactive (IC 50 = 133.8 μg/ml) against CQ resistant P. falciparum (K1) [ 46 ]. The possible reason for the contradictory results could be due to the differences in the duration of incubation in antiplasmodial assay.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…In this study, the good level of antiplasmodial activity showed by the MeOH extract of E. scaber leaf (EC 50 = 0.27 μg/ml) was contradictory to the study reported by Kantamreddi and Wright [ 46 ]. According to Kantamreddi and Wright [ 46 ], the MeOH extract of the leaves of this plant was considered inactive (IC 50 = 133.8 μg/ml) against CQ resistant P. falciparum (K1) [ 46 ]. The possible reason for the contradictory results could be due to the differences in the duration of incubation in antiplasmodial assay.…”
Section: Discussioncontrasting
confidence: 94%
“…The present study has identified the antiplasmodial activity in selected plant extracts by HRP2-based assay or HRP2 ELISA technique. There are other reports on antiplasmodial studies using different screening methods such as WHO schizont maturation test [ 44 ], isotopic assay [ 45 ], pLDH enzymatic assay [ 46 , 47 ], SYBR Green I assay [ 48 50 ] or fluocytometric assay [ 51 ]. Briefly, the HRP2-based assay is a very sensitive and specific measures of P. falciparum growth by quantifying parasite specific biomolecule, HRP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 80% of the world population still primarily rely on herbal drugs. 1 In India, Ayurvedic medicines were widely considered due to affordability and availability in local markets. Also, the demand for Ayurveda drugs in Western market has increased tremendously which draw attention to the need of quality of Ayurvedic products.…”
Section: Introductionmentioning
confidence: 99%
“…1 Herbal drugs are gaining popularity worldwide, and there are many branded and unbranded formulations are available for therapeutic and cosmetic uses. 2,3 But, the cases of adverse health consequences caused by the use of herbal medicines have also been increasing simultaneously.…”
Section: Introductionmentioning
confidence: 99%